Evaluasi Kinerja Insulasi Pipa Uap Panas Fire Tube Boiler Pada Industri Kilang Minyak Dan Gas - Siahaya, Delsi Natalia; Hatuwe, Azmain. N.; Malakauseya, Jeffrie J (Jurusan Teknik Mesin, 2024)
The steam pipe fuctions as a conduit for hot steam from the boiler to other unit. During the transport process in the pipe, it is expected that heat loss from the steam in minumized, so that the required on the steam pipe unit in need. Therefore, hot pipes need to be insulated. In this study, the insulation on the steam pipe is mae of rock wool with a thickness of 7,5 cm. After a long period of operation, it is necessary to evaluate the insulation perfomance in retaining the rate of heat loss. The method used in this research in theoretical review, where the data is obtained from field observations and then analyzed using equations from supporting references. From the discussion results, it is found heat loss in the pipe occurs through conduction and convection, also influenced by variations in ambient temperature. The average total heat loss is 15,715.90 Watts. The percentage of heat loss compared to the total steam transported through the pipe is 0,3376% on average, and the insulation perfomance in preventing heat loss is considered still effective. Keywords: Insulation,Boiler, Steam pipe,Refinery.